OPTIMASI EFISIENSI JALUR TRANSPORTASI KAMPUS MENGGUNAKAN PENDEKATAN TEORI GRAF - Fitri, Legita Aulia Syah; Pratiwi, Nadya Ayu; Zaharah, Siti; Pramudia, Jihan; Wati, Dwi Yasinta; Fadhila, Sesaria; Darwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Universitas Muhammadiyah Kotabumi campus is located on Jalan Sindang Sari, an area that serves as a hub for both local economic activity and higher education. However, high traffic volume causes congestion issues for students commuting to the campus. This study employs graph theory to determine the most efficient route—in terms of travel distance—from Jalan Raya Kembang Gading (Dusun Rejosari, RT 001/RW 002, Abung Selatan District, North Lampung Regency, Lampung Province) to the Universitas Muhammadiyah Kotabumi campus (Jalan Hasan Kepala Ratu 1052, Sindangsari, Kotabumi, North Lampung). Dijkstra's algorithm is the specific method utilized for this research. The analysis demonstrates the utility of graph theory in identifying alternative routes, traffic congestion points, and capacity upgrade requirements, thereby providing a foundation for efficient and sustainable urban transportation planning decisions.